Utilization of shopfloor management as a tool for communication and knowledge sharing in the framework of LEAN logistics – a case study - Benyahya, Petra; Macurová, Lucie (Serbian Journal of Management, 2021)
The study investigates whether establishing of the shopfloor management in the company is beneficial for the company or not even in difficult conditions (food production with BRC standards of production, presence of foreigners, agency employees). A qualitative research based on detailed long-term observation the real process of planning and establishing the shopfloor management in the company was used, as well as interviews with industrial engineers, first line managers, blue-collar workers, and shopfloor management practitioners. The company was chosen for this case study on purpose. The findings say it was good to establish SFM in the company. In spite of obstacles, the utilization of machines increased by 20% and one machine (out of 12) could be sold due to redundancy. The need for human capital decreased, the number of scraps decreased, and the cooperation improved.
Keywords: shopfloor management, cooperation, communication, lean culture tool